Suppose f(x)= sqrt x^2+6x+10 and g(x)= 9x+8

(f(g(x))=

(f(g(x)(-2)=

1 answer

To solve (f(g(x)):

Substitute g(x) into f(x):
f(g(x)) = sqrt((9x+8)^2 + 6(9x+8) + 10)

To solve (f(g(x)(-2)):

Substitute g(x)(-2) into f(x):
f(g(x)(-2)) = sqrt((-2)^2 + 6(-2) + 10)
Similar Questions
  1. Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work.sqrt(7)*sqrt(x)-sqrt(7)*7*sqrt(7) sqrt(7*x)-7*sqrt(7*7) sqrt(7x)-7*sqrt(7^2)
    1. answers icon 1 answer
  2. sqrt 6 * sqrt 8also sqrt 7 * sqrt 5 6.92820323 and 5.916079783 So you can see the steps — sqrt 6 * sqrt 8 = sqrt 48 sqrt 7 *
    1. answers icon 0 answers
    1. answers icon 1 answer
  3. Find the distance between these two points using the Pythagorean Theorem.Which choice is correct? (1 point) sqrt(6 ^ 2) + 3 ^ 2
    1. answers icon 1 answer
more similar questions